Testing a novel account of the dissociation between self‐reported memory problems and memory performance in chemotherapy‐treated breast cancer survivors. Issue 1 (10th February 2017) - Paquet, Lise; Verma, Shailendra; Collins, Barbara; Chinneck, Anne; Bedard, Marc; Song, Xinni
Abstract: Background: A puzzling observation pertaining to the impact of breast cancer on memory is the frequently reported dissociation between breast cancer survivors' self‐reported memory problems and memory performance. We evaluated the hypothesis that the dissociation is related to the fact that the objective memory measures previously used assessed retrospective memory (RM) and did not tap prospective memory (PM), a domain about which survivors are complaining. Methods: In a case‐healthy‐control (N = 80) cross‐sectional study, the Memory for Intention Screening Test was used to assess PM and the Wechsler Logical Memory Test was used to evaluate RM. Self‐reported problems were assessed with the Prospective and Retrospective Memory Questionnaire. Measures of depression (Center for Epidemiologic Studies Depression Scale) and fatigue (Functional Assessment of Cancer Therapy: Fatigue) were also administered. Results: Both groups reported more PM than RM problems ( P < .001). Survivors reported more fatigue and depression symptoms and more memory problems than controls (all P < .001). Importantly, the group difference in self‐reported problems was no longer observed after adjusting for depression and fatigue. Survivors performed worse than controls on both PM and RM tasks. In neither group, however, were associations between self‐reported RM and PM problems and RM and PM objective performance observed. Conclusions: Breast cancer survivors exhibit PM and RM deficits, which do not correlate with self‐reported memory problems. Although unrelated to performance, memory complaints should not be dismissed, as they are closely associated with depression and fatigue and reveal an important facet of the cancer experience.